Karl Marx and the close of his system, and Böhm-Bawerk's criticism of Marx, by Rudolf Hilferding. Together with an appendix consisting of an article by Ladislaus von Bortkiewicz on the transformation of values into prices of production in the Marxian system. Ed. with an introd. by Paul M. Sweezy (Kelley, 1949)
Index.